THE UTILIZATION OF NON-ORGANIC WASTE TOWARDS KAMPUNG SAYUR TO EMPOWER THE WASTE BANK IN KAMULYAN - Isana Arum Primasari; Hayati Mukti Asih (Universitas Ahmad Dahlan, 2021)
Waste is a problem in environment and society that has never been resolved. One of the triggers for waste is the use of disposable product packaging. Reducing single-use waste by reusing it will impact reducing waste generation so that the city becomes clean. Reuse of waste by making it the basic material for an innovative product will add value to waste to no longer pollute the environment. The existence of the Kampung Sayur program in Brontokusuman has made waste no longer underestimated. The location of Brontokusuman in the middle of a densely populated city is an obstacle in implementing “the vegetable village” program so that the need for community empowerment in managing waste wisely. The community empowerment program implemented in Brontokusuman aims to provide education to the community in managing waste. organic and non-organic wisely.Therefore, the training of vertical garden was conducted to support that program